Management of Oral Hygiene Health Education with Animated Video Media on Improving Knowledge of Families and Pediatric Patients - Oktaviana Dwi Kartikasari; Nurfika Asmaningrum; Dicky Endrian Kurniawan; Fitri Chandra Kuspita (KHD Production, 2026)
School-age children are susceptible to disease and need health supervision. Children who are sick have a high dependence on others in terms of self-care. Children who are sick and unable to fulfill their self-care will experience self-care deficit problems. One component of personal hygiene often forgotten when self-care during illness oral hygiene is. This study aims to determine how health education using animated video media on oral hygiene can improve family and patient knowledge of self-care, especially oral hygiene. This research is a descriptive, quantitative study that uses a case study approach. The research design was a one-group pre-test-post-test design, in which a knowledge questionnaire was administered before and after health education. There are differences in knowledge scores before and after health education is provided to both families and patients, with increased knowledge of oral hygiene. Evaluation of oral hygiene using the OHI-S score shows a decrease in score, indicating improvement from poor to moderate, and is performed 4 times every 24 hours until discharge. Providing oral hygiene education can increase parents' and patients' knowledge and interest in self-care.